2019
DOI: 10.3390/app9122443
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Natural Gypsum Materials and Their Composites for Building Applications

Abstract: Building retrofitting plays a key-role in energy saving and a growing interest is focused on insulating materials that allow a reduction in heat loss from envelopes with low thickness, by a process of reducing heating and cooling demand. In this context, a complete characterization of the physical properties of Moroccan natural gypsum materials was carried out. Basic information on the mineralogical, microstructure, thermal, mechanical, and acoustic characteristics of the rocks sampled from two Moroccan region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…The literature shows multiple methods to evaluate acoustic insulation, of which some are based on impedance tubes [ 35 , 50 ]. Transmission loss (TL) was measured according to the ASTM E2611—19 standard (“Standard Test Method for Normal Incidence Determination of Porous Material Acoustical Properties Based on the Transfer Matrix Method”) using a method developed at the Polytechnic School of Gandia and based on the impedance tubes test.…”
Section: Methodsmentioning
confidence: 99%
“…The literature shows multiple methods to evaluate acoustic insulation, of which some are based on impedance tubes [ 35 , 50 ]. Transmission loss (TL) was measured according to the ASTM E2611—19 standard (“Standard Test Method for Normal Incidence Determination of Porous Material Acoustical Properties Based on the Transfer Matrix Method”) using a method developed at the Polytechnic School of Gandia and based on the impedance tubes test.…”
Section: Methodsmentioning
confidence: 99%
“…Yu et al [21] studied the meso-structure evolution of gypsum at different salt concentrations at normal temperature, indicating significant changes in the meso-structure of gypsum crystals in different salt concentrations, affecting the physical and mechanical properties, especially permeability, extreme strength, and deformation characteristics. Bouzit et al [22] studied the conventional triaxial compression properties of anhydrite. Studies have shown that with increasing confining pressure, the deformation characteristics of anhydrite show a gradual transition from brittle to ductile nature, with peak and residual strength and confining pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of CaSO 4 takes place at 180 °C with a mass loss of 3.896%. 23,24 Particle size distribution…”
Section: Thermal Analysismentioning
confidence: 99%